Occupation-related cancer in urology—Current knowledge including environmental medical aspects Berufsbedingte Krebserkrankungen in der Urologie – aktuelle Erkenntnisse unter Einbeziehung umweltmedizinischer Aspekte - Golka, Klaus; Böthig, Ralf; Weistenhöfer, Wobbeke; Jungmann, Olaf P.; Bergmann, Steffi; Zellner, Michael; Schöps, Wolfgang (Journal für Urologie und Urogynäkologie, 2023)
Occupation-related cancers are of considerable importance, which is not yet adequately recognized in the field of urology. The three numerically most significant entities are tumors of the urinary tract caused by carcinogenic aromatic amines or polycyclic aromatic hydrocarbons, renal cell cancer after high exposure to the solvent trichloroethylene, and mesotheliomas of the tunica vaginalis of the testis after exposure to asbestos; however, these can only be recognized as occupation-related if an occupational history regarding the hazard relevant to the organ bearing the tumor is documented from the beginning of employment, e.g. by a questionnaire. This is because the relevant exposures generally date back several decades. With the exception of high exposure to trichloroethylene, the substances mentioned can also environmentally trigger the same tumors. In the context of environmental risk factors, it is of considerable importance that smoking is now considered to be a trigger for some 50% of all bladder cancers in men and women; however, smoking cessation results in a reduction in smoking-related cancer risk of over 30% after only 3–4 years. Work and commuting accidents, which are considered occupational risks, can lead to urological sequelae. For example, increased tumors of the bladder can occur after spinal cord injury lasting longer than 10 years.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Bladder cancer; Mesothelioma; Renal cell cancer; Second-hand smoking; Tunica vaginalis of the testis